PENGARUH MEDIA DAKON TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 68 PALEMBANG - Lingga Ariyandi; Ramanata Disurya; Tanzimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of dakon media on the mathematics learning outcomes of grade III students of SDN 68 Palembang with the material of the relationship between standard units of weight. This type of research is quantitative experimental research with a posttest only control design. With a sample of class III A and class III B totaling 44 students. With data collection techniques using tests and documentation. The results of the study in the control class obtained an average posttest score of 61.48, the data shows that the learning outcomes of the control class still do not meet the minimum completeness criteria for learning outcomes, which is 70. In the experimental class, the average posttest score was 76.56 and the data shows that the learning outcomes of the experimental class meet the minimum completeness criteria for learning outcomes. While the normality test shows that the posttest data of the two groups of students, namely the control class and the experimental class, have a data distribution that is normally distributed with a significant value in the control class of 0.96 and 0.84 in the experimental class. The results of the homogeneity test obtained were 0.963, greater than 0.05 and can be stated as homogeneous. In the hypothesis test of the t-test (independent sample t-test) obtained a sig value (2-tailed) of 0.004 < less than 0.025 then Ho is rejected and Ha is accepted. It can be concluded that there is an influence of the use of dakon unit media on the mathematics learning outcomes of grade III students of SDN 68 Palembang